Clear and Simple as the Truth Writing Classic Prose - Second Edition - Thomas, Francis-Noël; Turner, Mark (Princeton University Press, 2011)
For more than a decade, Clear and Simple as the Truth has guided readers to consider style not as an elegant accessory of effective prose but as its very heart. Francis-Noël Thomas and Mark Turner present writing as an intellectual activity, not a passive application of verbal skills. In classic style, the motive is truth, the purpose is presentation, the reader and writer are intellectual equals, and the occasion is informal. This general style of presentation is at home everywhere, from business memos to personal letters and from magazine articles to student essays. Everyone talks about style, but no one explains it. The authors of this book do; and in doing so, they provoke the reader to consider style, not as an elegant accessory of effective prose, but as its very heart.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 26. Nov 2019)
Keywords: LANGUAGE ARTS & DISCIPLINES / Composition & Creative Writing; English language -- Rhetoric; English language -- Style; Language and languages; Literature; Report writing